Weak gravitational lensing - Bartelmann, Matthias; Schneider, Peter (Physics reports, 2001)
We review theory and applications of weak gravitational lensing. After summarising Friedmann-Lemaı̂tre cosmological models, we present the formalism of gravitational lensing and light propagation in arbitrary space-times. We discuss how weak-lensing effects can be measured. The formalism is then applied to reconstructions of galaxy-cluster mass distributions, gravitational lensing by large-scale matter distributions, QSO-galaxy correlations induced by weak lensing, lensing of galaxies by galaxies, and weak lensing of the cosmic microwave background.
Published online: 12 December 2000
Gesehen am 27.09.2017